Fetal Alcohol Spectrum Disorders in Adults: Consensus on Diagnosis and Position on Care and Research in Germany Fetale Alkoholspektrumstörungen bei Erwachsenen Konsens zur Diagnostik und Position zu Versorgung und Forschung in Deutschland - Schecke, Henrike; Wagner, Jessica; Richter-Schmidinger, Tanja; Bolbecher, Gisela; Michalowski, Gisela; Landgraf, Mirjam N.; Feldmann, Reinhold; Zimmermann, Ulrich; Wolter, Heike; Schwerg, Lina; Kruse, Björn; Becker, Gela; et al. (Sucht, 2024)
Background: With an estimated prevalence of 1 to 2 per 100 people, Fetal Alcohol Spectrum Disorders (FASD) are common in Europe and are associated with a high burden for people with FASD, their relatives and the society. They are complex disorders with limitations at various levels, including behavior, performance and independence. An S3 guideline is available for the diagnosis of FASD in children and adolescents. Aim: We present an author consensus on the diagnosis of FASD in adults. Conclusions: In addition to the weaker evidence for adulthood, a major problem is that only a few locations offer appropriate services. The result is an inadequate diagnostic and care structure in Germany. The following four approaches can be taken to improve the situation: (1) More consistent use of available screening tools in general medical, psychiatric and psychotherapeutic care; (2) Establishment of additional specialized diagnostic centers; (3) Establishment of additional specialized treatment and residential facilities; and (4) Promotion of research on FASD across the lifespan. These steps will lead to an improvement in the treatment and care of people with FASD.
CRIS-Team Scopus Importer:2024-10-25
Keywords: diagnostic; FASD; screening; therapy